Virality, Justice and the Principle of “Blocking the Means to Evil” - Tanzilulloh, M. Ilham; Agmar, Khoirun Nisa Aprilian (De Jure: Jurnal Hukum dan Syari'ah, 2024)
Social media virality can expedite the resolution of legal cases, but it is not a suitable foundation for attaining genuine justice in Indonesian law enforcement because it can lead to inequality and human rights violations, particularly when viewed through the lens of Islamic law, which places a strong emphasis on preventing injustice. This research explains how the virality of social media affects the existence of a just legal construction from the perspective of Islamic law. Combining juridical and empirical approaches, this research draws on primary data from viral cases in several journal articles, analysed using the normative-qualitative method. Legal materials used to analyse data include primary legal materials, such as laws and regulations, secondary legal materials in textbooks containing legal theories and reasoning, and journals. The research results are presented in descriptive-analytical form. The results of this study reveal that although viral legal cases receive faster attention, the phenomenon of "no viral no justice" cannot ensure the achievement of true justice. This concept contributes to unequal case handling and risks violating individual rights. By examining the connection between social media virality and justice in Indonesian law enforcement, this research integrates Islamic law principles, particularly the concept of “blocking the means of evil” (saddu al-dzari'ah), emphasising the prevention of damage resulting from injustice. This research offers an approach to understanding the impact of social media virality on the legal process, highlighting how social media can influence public perception and, in turn, legal decisions.